Audiodescrição didático pedagógica para educadores - Pimentel, Silvia Janaina de Oliveira (Brasil, 2023)
The multidisciplinary thematic notebook, proposed here, is intended for visually impaired students inserted in inclusive high school classes, without, however, being restricted to this public. (Division). Audiodescription is a communication accessibility resource for people with visual impairment that aims to describe the information of images in words, based on Mota (2012, 2016), Mianes (2016), Lima (2010, 2013) Perdigão (2017) and Vergara Nunes (2016). It has parameters already established, from contexts in which it has been employed, and these have served as guidance for its use in other spaces, Filho, Machado, Nunes (2017) and Ribeiro(2020), among them, that of teaching, Nunes (2016). To be accessible to teaching, it is understood that there is a need to think about other parameters for this area, since those that exist do not dialogue directly with didactic-pedagogical issues, bringing implications for student learning. In this context, the proposal brings the Didactic-Pedagogical Audio Description, which has the transversal characteristics to the teaching/learning of visually impaired students in inclusive classrooms.